Laboratory Investigation of Indigenous Consortia TERIJ-188 for Incremental Oil Recovery - Sharma, Neha; Lavania, Meeta; Kukreti, Vipin; Rana, Dolly Pal; Lal, Banwari (Frontiers in Microbiology, 2018)
Bacterial Profile modification is an efficient process which brings the alteration in permeability of the porous media of the reservoir by selective plugging which eventually recover the residual oil. It is an advantageous and feasible method for residual oil recovery from high permeability zones of the reservoir. In this study, indigenous bacterial consortia, TERIJ-188 was developed from Gujarat oil fields. TERIJ-188 was identified as Thermoanaerobacter sp., Thermoanaerobacter brockii, Thermoanaerobacter italicus, Thermoanaerobacter mathranii, Thermoanaerobacter thermocopriae. The novelty of consortia was that it produces biomass (850 mg l-1), bio-surfactant (500 mg l-1), and volatile fatty acids (495 mg l-1) at 70ºC in the span of 10 days, which are adequate to alter the permeability and sweep efficiency of high permeability zones facilitating the displacement of oil. The biosurfactant was analyzed for its functional group by FTIR and NMR techniques which indicate the presence of C-N bond, aldehydes, triacylglycerols. TERIJ-188 showed an effective reduction in permeability at residual oil saturation from 28.3 to 11.3 mD and 19.2 % incremental oil recovery in a core flood assay. Pathogenicity test suggested that TERIJ-188 is nontoxic, non-virulent and safe for field implementation.